Efektivitas Aplikasi Sistem Informasi Sumberdaya Terintegrasi Terhadap Pembayaran UKT Mahasiswa - Karimah, Nadzirotul; Nikmah, Tiara Iftitahun; Yulianti, Dwi Rizfiya; Haerani, Alfara; Hidayat, Rofiq (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to identify and analyze how effective the sister application is in paying UKT for UIN KHAS Jember students. This research uses quantitative research methods and comparative causal research. Data collection was obtained from an online questionnaire, which was distributed to 30 students of the Islamic Education Management (MPI) study program at UIN KHAS Jember. The sample was selected using a simple random sampling method. The results of data analysis show that the items in the questionnaire are valid and reliable. The classical assumption test shows that there are no problems of normality, heteroscedasticity and multicollinearity. Hypothesis testing through simple linear regression shows that the sister application has a significant and positive effect on UKT payments for UIN KHAS Jember students. Based on the results of this analysis, it was concluded that the sister application was effectively used for paying UKT for UIN KHAS Jember students.